Elderly's Mobility to and from Work in the US: Metropolitan Status and Population Size - J. Ignacio Gimenez-Nadal; José Alberto Molina; Jorge Velilla (Institute of Labor Economics (IZA), 2020)
This paper explores the mobility patterns of elder workers in the United States, with a focus on mobility to and from work (e.g., commuting) across metropolitan areas and metropolitan population sizes. Using detailed time diaries from the American Time Use Survey for the years 2003-2018, estimates reveal a positive correlation between the time spent commuting and residing in metropolitan areas, which is also driven by longer commutes in more populated metropolitan areas. Furthermore, elder workers in metropolitan areas of more than 2.5 million inhabitants use more public transports in their commuting trips than similar workers in less-populated or non-metropolitan areas. The analysis presented here may allow policy makers to identify which elder workers may be more affected by the negative consequences of commuting, and also which groups of elder workers have more limitations in their commuting behaviors.
Keywords: R40; J14; 330; commuting time; elder workers; metropolitan areas; population size; American Time Use Survey